2012
DOI: 10.1002/jms.3103
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous quantitation of IC87114, roflumilast and its active metabolite roflumilast N‐oxide in plasma by LC‐MS/MS: application for a pharmacokinetic study

Abstract: A sensitive and reliable high-performance liquid chromatography-mass spectrometry (LC-MS/MS) was developed and validated for simultaneous quantification IC87114, roflumilast (RFM), and its active metabolite roflumilast N-oxide (RFN) using tolbutamide as an internal standard. The analytes were extracted by using liquid-liquid extraction and separated on a reverse phase C(18) column (50 mm × 3 mm i.d., 4.6 µ) using methanol: 2 mM ammonium acetate buffer, pH 4.0 as mobile phase at a flow rate 1 mL/min in gradient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Because of the short half life of the PI3Kδ inhibitor used (53), the results of PI3Kδ inhibition in vivo are likely due to proximal effects on DC-mediated sensitization which occurs over the first 24 - 72 h (54), but additional effects on the activation of T cells or B cells cannot be excluded. Several previous studies have demonstrated a role for PI3Kδ in the effector phase of antigen-induced allergic pulmonary inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the short half life of the PI3Kδ inhibitor used (53), the results of PI3Kδ inhibition in vivo are likely due to proximal effects on DC-mediated sensitization which occurs over the first 24 - 72 h (54), but additional effects on the activation of T cells or B cells cannot be excluded. Several previous studies have demonstrated a role for PI3Kδ in the effector phase of antigen-induced allergic pulmonary inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of roflumilast and its metabolite was performed by liquid chromatography tandem mass spectrometry (LC-MS-MS) using the analytical procedures and conditions previously described(23). In addition, in a subset of patients, 543 single nucleotide polymorphisms (SNPs) from 69 distinct genes involved in drug absorption, distribution, metabolism, and excretion (ADME) were analyzed by massively parallel sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma and brain were frozen at À80 1C until compound level determination took place. The concentrations of roflumilast and roflumilast N-oxide in plasma and brain were measured using a gradient LC/MS/MS procedure as described previously (Thappali et al, 2012). For rolipram, 200 ml plasma/brain homogenate (80:20 acetonitrile and water) were vortexed with 200 ml of acetonitrile for 60 sec.…”
Section: 5mentioning
confidence: 99%